Impulse ventilation for pollution control in underground car parks - Viegas, J. (2009)
Impulse ventilation systems (IVS) have been used for years to provide longitudinal ventilation in tunnels. In last 15 years these systems have been applied also to underground car parks. However, the design of such systems is not yet well defined and their performance was never compared to ducted ventilation systems. A research project on this subject is presented and the preliminary results of the survey of ventilation relevant quantities in enclosed car parks in use (project task 1) are also presented. Results show that the first predictions of carbon monoxide average concentration are compatible with measurements and that some peaks of CO concentration occur. The activation of jet fans and increment of ventilation rate dilute very fast the pollution peaks. Pollution peaks seem to be associated to local concentration of vehicle engines working or working close to CO detectors.